(3OjhGf GdCHjhQOj (B((3bSe GdYQGbjGJ(B)s - (3CHhGdeXaQ eMeO Hf CMeO Hf eMeO Hf eYGhjI GdCUZQ GdCehj GdCHjhQOj,J (B557 (3g` s ((3NhGQRe s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi fYeI ZfGA GdeQGO, hefMI eJUdI GdEeOGO, aEf GdTYQ OjhGf GdYQH, hJQLeGf GdCOH, hbO Qhi Cfg HefRdI GdcdGe s
(3BNQgG (B:s
(3YLHJ ef GKfjf GSJVjYG hCLMaJ HbOQ QHgeG CjOj GdNWhH GdahGOM ef GHf cQje de JUHg NUGU hef Cfhj ddCQGRd eGOM s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B209s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B17 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B774s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(370) s
Keywords: (3GdCOHs